Take-Home: Communication Skills Can Be Taught - Karunathilake, I.M.; Witharana, C. (Springer Nature, 2020)
Effective communication is a key essential in clinical practice. The practice of good communication skills is of utmost importance for the development of a trustworthy relationship between the doctor and the patient. It also results in benefits such as reduction in errors and better compliance leading to cost effectiveness. Since many litigation cases occur due to medical errors, communication plays key role in preventing such cases. While patients will derive better care, the health professionals are likely to have better job satisfaction [1, 2]. On the other hand, ineffective communication has been one of the main reasons for growing dissatisfaction among patients and the general public.
Keywords: Communication